STRUCTURAL AND ELECTRONIC PROPERTIES OF THE SUPERCONDUCTOR [Y(0.8)CA(0.2)](BA(0.5)SR(0.5))2CU3O7-δ - Poma M., G. F. (2012)
In this work we report the structural and electronic properties of the compound [Y0.8Ca0.2](Ba0.5Sr0.5)2Cu3O7-δ (YCaBaSr) which is a superconductor below the critical temperature TC = 80 K. This compound was prepared using the Sol-Gel method. The structural properties were studied by X-ray diffraction and electronic properties were studied by X-ray Photoemission Spectroscopy (XPS). The results were compared with those ones of the traditional superconductor YBa2Cu3O7-δ (YBCO). The X-ray photoemission spectra were taken at room temperature (normal state) and at 30 K (superconductor state). In the superconductor state, the X-ray photoemission spectra showed a shift in the O 1s. While the position of the Cu3p principal peaks do not change when measuring at 30 K. However, the spectra reveal the appearance of a new peak due to de hybridization of the Cu3d and O2p states. In addition, the Fourier map of the crystal structure of YCaBaSr obtained by Rietveld refinement is provided.